The Influence of Visual Merchandising on Store Patronage in the Fast-Fashion Stores in Indonesia: The Role of Shopping Value and Self-Congruity - Ogi Dhaneswari Daraninggar; Serli Wijaya; Hatane Semuel (Gadjah Mada International Journal of Business, 2020)
The study examined direct and indirect effects of visual merchandising on store patronage in a fast-fashion retail context. Adopting the Stimulus-Organism-Response (S-O-R) theory, this study aimed to investigate the relationships of visual merchandising, self-congruity, consumers’ perceived shopping value in determining store patronage. While studies about fast-fashion and store patronage behaviour have been extensively conducted in various market regions, research in an emerging middle-income country like Indonesia is still in its scarcity. The study is therefore among a few attempts to better understand the Indonesian consumers’ buying behaviour of fast-fashion brands. A survey was completed to 250 fast-fashion store shoppers in Surabaya, the second largest city and well-known shopping tourism destination in Indonesia. Partial Least Squares (PLS) path modelling method was utilised to estimate the proposed structural model. The results revealed that visual merchandising, shopping value, and self-congruity had positive and significant effects on store patronage. The study has also found that the indirect effects of consumers’ perceived shopping value and self-congruity as mediating variables as to how visual merchandising affected store patronage, were stronger than the direct ones. Managerial implications based on the findings and recommendations for further research were described.